Post-surgical adhesions are triggered by calcium-dependent membrane bridges between mesothelial surfaces - Adrian Fischer (Nature Portfolio, 2020)
Surgical adhesions are organ-joining bands of scar tissue that remain clinically untreatable. Here, the authors show that adhesions are formed through expansive mesothelial membrane bridges, and that blocking these with small molecules prevents formation of adhesions in mice.